The Role And Function Of Mantau Arts In The Community Of Merangin District, Jambi Province - Zaidi, Ahmad; Syaputra, Weldi (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
Mantau is a traditional music from Bangko District, Merangin Regency, Jambi Province. Mantau historically comes from a rhyme song carried by the Anman tribe who arrives at the port of Central Sumatra Island. The performance of mantau is sung by one person and the poems are arranged spontaneously into a rhyme form. Mantau underwent several changes on it’s performance, such as the formation of players, and the addition of musical instruments. In the past, mantau was only sung by one person, both male and female, but now mantau can be sung by two or more peoples, both male and female, from children, teenagers, to adults. The musical instruments are also varied. Nowaday mantau uses other musical instruments such as violin, drum, gong, and wooden kelintang for the vocal accompaniment which previously did not exist in mantau. Uniquely mantau music still survives and popular for it's community. This study seeks to see how mantau can survive and analyzed it through the musical aspect as well as the social aspect. The theory used to answer the problem proposed in this study is the